n-power-Posinormal Operators - El Moctar, O. B. (Methods of Functional Analysis and Topology, 2021)
B(H) will denote the algebra of all bounded linear operators on a complex Hilbert space H. In [6], the authors proved that natural power of a posinormal operator is not in general posinormal. Precisely, they constructed an example of a posinormal operator with square not being posinormal. Given a positive integer n, the aim of this article is to study a class of operators in B(H) called n-power-posinormal. This class is invariant under natural power and contains any natural power of any posinormal operator and all n-power normal operators. Позначимо через B(H) алгебру всіх обмежених лінійних операторів у комплексному гільбертовім просторі H. У [6] доведено, що цілий степінь позінормального оператора не обов’язково є позінормальним. Зокрема, був наведений приклад позінормального оператора, квадрат якого не є позінормальним. Метою цієї статті є дослідження класу n-степенево позінормальних операторів з B(H), інваріантного відносно натуральних степенів, який містить натуральні степені позінормальних операторів та n-степенево нормальні оператори.